Governance in international trade: Judicialisation and positive integration in the WTO - Dirk De Bièvre (Max Planck Institute for Research on Collective Goods, 2004)
Positive integration among states, defined as the correction of negative externalities from liberalisation, is generally assumed to be very difficult to achieve on the European level, let alone on the international or global level. The political transaction costs of achieving positive integration legislation indeed seem daunting in an organisation such as the World Trade Organization (WTO), which operates under conditions of unanimity and has a membership of over 140 sovereign states. Yet, member states seem to have crossed the Rubicon: They have concluded a number of agreements that impose positive obligations to adopt new policy measures in fields traditionally restricted to the sovereign nation-state. There has been consistent political pressure to graft other, non-trade issues onto the WTO framework, i.e. to enlarge an organisation that formerly dealt exclusively with trade into a governance structure that also has regulatory competences in other areas of public policy. WTO member states have indeed introduced the obligation to protect intellectual property rights internationally, and they have concluded agreements on health, on technical barriers to trade, and on investment - each of these being fields of public policy for which more specialised agencies within the United Nations system would seem to have been the more natural locus for such agreements. Further, there have been - hitherto unsuccessful - calls to bring labour rights, environmental standards, or competition policy under the jurisdiction of the WTO. This raises the question: why and under which conditions is positive integration possible in the WTO? The present paper seeks to formulate theoretically embedded hypotheses that answer this question. I argue that judicialisation - the presence of binding third party enforcement - makes every single WTO commitment more credible. Because judicialisation facilitates enforcement, it exerts force on political actors in the legislative arm of the organisation to bring positive integration issues under the jurisdiction of the WTO. The aim of this paper is to explore the explanatory force of this general hypothesis in empirical cases of positive integration (intellectual property, health, technical barriers to trade, and investment) and to come to new theoretical and empirical insights about the sources of and conditions for international cooperation. This paper thus aims to contribute to interdisciplinary research on judicialisation in international trade governance and the impact of judicialisation on the emergence of global governing structures.
Keywords: 330; WTO-Regeln; Wirtschaftsintegration; Handelsliberalisierung; Internalisierung externer Effekte; Internationale Schiedsgerichtsbarkeit; Welt; Global Governance